2006
DOI: 10.1063/1.2400699
|View full text |Cite
|
Sign up to set email alerts
|

Quantum creep of β–Sn in the normal and superconducting states. Influence of the NS transition on work hardening

Abstract: Previously we investigated the kinetics of transient logarithmic creep of ␤-tin single crystals at very low temperatures 0.5 K Ͻ T Ͻ 4.2 K with the sample under deformation in the normal ͑N͒ electronic state. In a continuation of that research, here we determine the boundary temperature T g Ϸ 1.3 K separating the regions of thermally activated ͑T Ͼ T g ͒ and quantum ͑T Ͻ T g ͒ plasticity governed by the motion of dislocations through Peierls barriers. Experiments are done on samples in the superconducting ͑S͒ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[6][7][8][9] The behavior of the following parameters was studied: the total increment in the creep deformation De, its fluctuating rate _ e m in the dynamic stage; and, the coefficient of logarithmic creep a.…”
Section: Parameters and Dependencesmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] The behavior of the following parameters was studied: the total increment in the creep deformation De, its fluctuating rate _ e m in the dynamic stage; and, the coefficient of logarithmic creep a.…”
Section: Parameters and Dependencesmentioning
confidence: 99%
“…Creep in single-crystal b-tin owing to the transition of this metal from the normal into the superconducting state (the NS transition) has been studied experimentally and theoretically in a series of papers. [6][7][8][9] These studies showed that the creep curves stimulated by the NS transition have a complicated stage structure including short-term dynamic sections with an exponential time dependence of the creep deformation and prolonged sections corresponding to fluctuation movement of dislocations in the crystal where the creep has a logarithmic time dependence. When the temperature is lowered the deformation in the logarithmic stage forms a small part of the overall increment and most of it occurs in the dynamic stage.…”
Section: Introductionmentioning
confidence: 99%